OSTEOINDUCTIVE CAPACITY OF PLATELET-RICH FIBRIN VS BIODENTINE FOR MANDIBLE FRACTURE - Marda Agung Nugraha; Indra Mulyawan; Ardian Jaya Kusuma Amran (Majalah Biomorfologi, 2024)
Highlights Biodentine has undergone thorough research as a bone grafting substance due to its ability to promote bone regeneration and effectively treat root or tooth fractures. PRF and Biodentine can stimulate osteogenesis, affecting bone repair, particularly in mandibular fractures.   Abstract Background:  Mandibular fracture is one of the most common fractures. The most common treatment for mandibular fractures is fixation. Therefore, xenogeneic agents such as platelet-rich fibrin (PRF) and Biodentine accelerate the reparative process. Biodentine is an interesting active ingredient that can induce bone regeneration. PRF and Biodentine can promote bone healing, but no literature discusses the differences between PRF and Biodentine osteoinduction mechanisms in treating mandibular fractures. Objective:  This article aimed to compare the effect of osteoinductive PRF with Biodentine for mandibular fractures. Material and Method: The research was conducted as a scoping review by performing a thorough search of the PubMed, Scopus, Science Direct, Elsevier, and Google Scholar databases. The study was obtained based on literature studies in the form of journals and textbooks in the last ten years (2013-2023). Result: The osteoinductive effect and mechanism of Biodentine in enhancing bone repair are likely correlated with releasing biologically active ions from calcium silicate cement and stimulating gene expression Runx-2. PRF has an osteoinductive role, causing the mechanism of releasing growth factors such as PDGF, VEGF, TGF-β, and IGF that promote the osteogenic process. Conclusion: There was no significant difference in the osteoinduction effect of PRF and Biodentine because these materials have different mechanisms of action for bone repair.